NATIONAL AND RELIGIOUS VALUES IN THE MODERN INFORMATION SPACE: ANALYSIS AND PRACTICAL RECOMMENDATIONS (Western European Journal of Historical Events and Social Science, 2026)
This article analyzes the significance of national and religious values in the modern information environment, their preservation and development among youth. The study examines information acquisition practices through social networks, the promotion of national and religious values in the virtual environment, as well as the impact of uncontrolled information flow on moral stability. Additionally, the article provides scientific and practical recommendations for forming national consciousness and maintaining spiritual immunity in the modern information space